Neurocysticercosis in Children with Seizures: A Cross-Sectional Study - Murli Manohar Gupta; Nagendra Chaudhary; Santosh Pathak; Nikhil Agrawal; Jaydev Yadav; Sandeep Shrestha; Om Prakash Kurmi; Baldev Bhatia; Kailash Nath Agarwal (International Journal of Pediatrics)
Background. Neurocysticercosis (NCC), a common cause of seizures in children from low and middle income countries (LMICs), if not diagnosed and treated early enough may lead to considerable morbidity and mortality. There is a lack of data on the prevalence of NCC and its clinical characteristics among those with seizure in South-Western Nepal. Aims and Objectives. To study the prevalence and clinical characteristics of NCC in children with seizures. Material and Methods. All children admitted to Universal College of Medical Sciences, a tertiary hospital in South-Western Nepal with seizures during 2014–16, were tested for NCC. NCC was diagnosed by neuroimaging [computerized tomography (CT) scan or magnetic resonance imaging (MRI)]. We used logistic regression to test the association between NCC with participants’ characteristics and clinical symptoms. Results. Among 4962 in-patient children, 168 (104 boys and 64 girls) had seizures (138 with generalized tonic clonic seizures (GTCS) and 30 with focal seizures). 43% of children with seizures had CT scan confirmed NCC. The prevalence of NCC in the oldest children (13–16 years) was significantly greater (57.1% versus 15.6%) compared to the youngest (0–4 years) one (p<0.001). Among 72 children with NCC, the proportions of children with vesicular, calcified, and colloidal stages were 76% (n=35), 18% (n=13), and 6% (n=2), respectively. Children with focal seizures had 13% more NCC compared to those with GTCS but the result was statistically not significant. The adjusted odds of having NCC among 5–8 years, 9–12 years, and 13–16 years children were 6.6 (1.78–24.60), 11.06 (2.74–44.60), and 14.47 (3.13–66.96), respectively, compared to 0–4-year-old children. Reoccurrence of seizures within the first 3 months of taking antiepileptic drug in those with NCC was approximately 3 times higher compared to those without NCC (11% versus 4%, p=0.084). Conclusions. This study shows that NCC contributes significantly to higher prevalence of seizures in children in South-Western region of Nepal.